Production of monoclonal antibody against Ompa protein of Candidatus Liberibacter asiaticus causing citrus greening disease - Thuong, Ho Thi; Thom, Nguyen Thi; Tra, Nguyen Thi; Vy, Trinh Thai; Ngoc, Pham Bich; Son, Le Van; Ngoc, Nguyen Thi Bich; Chu, Ha Hoang (Vietnam Journal of Biotechnology, 2020)
Citrus Greening, also known as HuangLongbing (HLB), is considered one of the most dangerous citrus diseases, and limiting the production of citrus trees all over the world. Production of antibodies against Ompa protein of Candidatus Liberibacter asiaticus (CLas) for detection of citrus greening disease is considered as promising research direction. In this study, for the purpose of producting antibodies against Ompa of CLas, we firstly used the camel VHH antibody library for screening VHH antibodies against Ompa using phage-display technique. Next, phages which had strong interaction with Ompa as shown in ELISA were selected for phagemid isolation and the DNA fragments encoding VHH antibodies were sequenced. The DNA fragment encoding the best VHH antibody was then selected and inserted into the expression vector pET-21a (+), then cloned in Ecoli DH5α strain and expressed in BL21 (DE3) strain. The expression of VHH antibodies against Ompa was optimized at different temperatures with an inductive concentration of 0.1 M IPTG. Anti-Ompa VHH antibodies were purified under denatured conditions then re-folded. The biological activity of the VHH antibody with Ompa antigen was assessed by indirect-ELISA reaction. Results indicated that the VHH antibody had a very strong interaction with the Ompa antigen. This opens up the prospect of applying VHH antibody in the detection of citrus greening disease.